Autoantibodies Against Perilipin 1 as a Cause of Acquired Generalized Lipodystrophy - Corvillo, Fernando; Aparicio, Verónica; López-Lera, Alberto; Garrido, Sofía; Araújo-Vilar, David; de Miguel, María P.; López-Trascasa, Margarita (Frontiers in Immunology, 2018)
Acquired generalized lipodystrophy (AGL) is a rare condition characterized by an altered distribution of adipose tissue and predisposition to develop hepatic steatosis and fibrosis, diabetes, and hypertriglyceridemia. Diagnosis of AGL is difficult and is based on the observation of generalized fat loss, autoimmunity, and lack of family history. The pathogenic mechanism of fat destruction remains unknown, but evidence suggests an autoimmune origin. Anti-adipocyte antibodies have been reported in patients with AGL; however, their involvement in the pathogenesis has been poorly studied, and the autoantibody target remains unidentified. Using a combination of western blot, immunoassays, and immunocytochemical studies, anti-adipocyte autoantibodies were investigated in patients with AGL, acquired partial lipodystrophy, localized lipoatrophy due to intradermic insulin injections, or systemic lupus erythematosus. The impact of these autoantibodies on the control of lipolysis was assessed in cultured mouse preadipocytes. Following this approach, we identified anti-perilipin 1 IgG autoantibodies in the serum of patients with autoimmune variety-AGL, but in no other lipodystrophies tested. These autoantibodies altered the ability of perilipin 1 to regulate lipolysis in cultured preadipocytes causing abnormal, significantly elevated basal lipolysis. Our data provide strong support for the conclusion that perilipin 1 autoantibodies are the cause of generalized lipodystrophy in these patients.